ANALISA FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM SEMBIRING TAHUN 2018 - Sri Sudewi Pratiwi Sitio (Jurnal Penelitian Kesmasy, 2020)
A nurse is someone who has the ability, responsibility and authority to carry out nursing care services at various levels of nursing services. Nursing services provided are in the form of nurse performance and must be based on high ability so that performance supports the implementation of tasks in nursing services. The purpose of this study was to determine the dominant factor related to the performance of nurses in the inpatient room of Sembiring General Hospital in 2018. This type of research was observational analytic with cross sectional approach where the population was all nurses in the inpatient ward of Sembiring General Hospital with a sample size 101 respondents were taken using proportional random sampling technique. Based on the results of the study it was found that from the variables of leadership, work performance, work promotion, incentives, working conditions, work relationships, and workload results obtained workload variables that were significantly related to the performance of nurses in the inpatient ward of Sembiring General Hospital with a value (p -value 0,004) with PR 1,698 (95% CI: 1,186-2,429) has a significant effect on the performance of nurses in the Inpatient Room of the Sembiring General Hospital. Based on the results of the logistic regression test, the most dominant variable was workload with a value (p-value 0.020) and Exp value (B) 2.939 (95%; CI: 1.185-7.291). It is recommended to the Head of the Sembiring General Hospital to pay more attention to the arrangements of nurses' work shifts, nurses' work rotations, job description job descriptions that are in accordance with the competencies and timeliness of nurses' entry and return from work so that in carrying out their work nurses can work effectively.